(untitled) (Research, Society and Development, 2021)
Eugenia punicifolia (Kunth) D.C., Myrtaceae, known as “pedra-ume-caá”, is popularly used in the treatment of inflammation, infections, fever, flu, diabetes, and diarrhea. This study aimed to carry out a comparative study of the chemical composition of volatile oil from E. punicifolia leaves collected in Goiás and Minas Gerais, as well as to evaluate the larvicidal activity against Aedes aegypti L3 larvae, the antimicrobial activity against bacteria, pathogenic fungi, and environmental, and cytotoxic activity to Balb 3T3 cells (murine fibroblasts). Volatile oils were obtained by hydrodistillation in a Clevenger apparatus and analyzed by Gas Chromatography Coupled to Mass Spectrometry (CG/MS). A total of 60 compounds were identified, the main components found in the leaves of Goiás being Germacrene D, bicyclogermacrene and β-longipenene and in the leaves collected in Minas Gerais they were (Z)-caryophyllene, γ-cadinene, spathulenol, caryophyllene oxide, and α-cadinol. The larvicidal effect was moderate against Ae. aegypti, with LC50 of 85.53 µg / mL for samples from Goiás and LC50 of 91.52 µg / mL for samples from Minas Gerais. Both oils showed moderate bactericidal activity against K. rhiziphyla (ATCC 9341), M. luteus (ATCC 10240), and S. aureus (ATCC 29737). The oils from Goiás (IC50 706.7 µg / mL) and Minas Gerais (IC50 160.7 µg / mL) had a lower cytotoxic concentration than the toxic action for larvae and bacteria, evidencing a safety profile and an interesting therapeutic potential, mainly concerning to volatile oil from Goiás. Therefore, the volatile oils from E. punicifolia leaves collected in Goiás and Minas Gerais that presented moderate larvicidal activity for Ae. aegypti also presented a bactericide activity and less cytotoxicity against murine fibroblasts. This is the first study of the larvicidal, antimicrobial and cytotoxic activity of volatile oils from E. punicifolia leaves.